The use of thermography in clinical Thoracolumbar disease in Dachshunds - Sargent, Gerald R. (Kansas State University, 2008)
Objective – To evaluate the value of thermography in a clinical setting for dogs with thoracolumbar disease. Animal Population – Thirteen client-owned short-haired Dachshunds presented to Kansas State University Veterinary Medical Teaching Hospital for paraparesis/paraplegia and diagnosed with thoracolumbar disease via myelogram/CT and confirmed during surgical decompression. Procedures - Thermal images were obtained with a hand-held infrared camera with a focal plane array uncooled microbolometer. Images were obtained after physical exam and client consultation and prior to any pre-anesthetic medications, approximately 30+ minutes after entering the hospital. Additional images were obtained in the same manner at 24 hour intervals following surgery until discharge. Six regions of interest (ROI) were identified and recorded. The ROIs identified were right and left thoracic, lumbar and pelvic regions. From each of these regions average temperatures were taken. Results - Temperatures in the pelvic region were significantly cooler (p< 0.001) over all days as compared to the thoracic and lumbar regions and to the overall mean temperature. The lumbar region temperature was significantly greater on day 0 as compared to thoracic and pelvic regions but was not significantly different on any of the following days. The thoracic temperatures were significantly greater than the lumbar and pelvic regions on day 2 but there was no significant difference on any of the preceding or following days. There was no significant difference between left and right on any of the days. There was a correlation of the pelvic region temperatures on day 3 in relation to the presenting neurological grade. Conclusion - Although there were varied heat patterns detected in dachshunds with IVDD, these patterns did not correlate with neurological grade, lesion site or lateralization of the lesion. Although there was a correlation between neurological grades and the pelvic region temperatures on day 3, this time period is unlikely to provide clinical utility. Clinical Relevance - The results of this study suggest that thermography is not a useful tool for the diagnosis or prognosis of thoracolumbar disease in dogs in a clinical setting.
Keywords: Thermography; Intervertebral disk disease; Dachshund; Thoracolumbar disease; Thermal imaging; Biology, Veterinary Science (0778)